2020
DOI: 10.20319/pijss.2020.62.0121
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Performance of Central Mindanao University Laboratory High School Students

Abstract: Several factors affect the performance of students. This investigation was conducted to find out the predictors of performance among students in the Central Mindanao University Laboratory High School (CMULHS). Results showed that CMULHS students performed well in English, Mathematics and Science in their elementary years. Their parents were actively involved in their children's school activities. They have slightly positive attitude towards schooling, fairly good study habits, highly motivated to study, and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…1 classes, decreased ability to concentrate, and lower energy levels which would result in a probability of failure, grade retention, and dropout (Shaw et al, 2015). Whereas, student's family background, including factors such as income level, parental education, and family support, involvement of parents with the things that their kids did at school except for gender, students are highly motivated to study, have fairly good study habits, have a slightly positive attitude toward education, and attribute their accomplishments to their efforts, and high students' performance (Balasico & Tan, 2020). Thus, parents have to pay attention and inspire their children to perform better in school.…”
Section: Global Journal Of Educational Studiesmentioning
confidence: 99%
“…1 classes, decreased ability to concentrate, and lower energy levels which would result in a probability of failure, grade retention, and dropout (Shaw et al, 2015). Whereas, student's family background, including factors such as income level, parental education, and family support, involvement of parents with the things that their kids did at school except for gender, students are highly motivated to study, have fairly good study habits, have a slightly positive attitude toward education, and attribute their accomplishments to their efforts, and high students' performance (Balasico & Tan, 2020). Thus, parents have to pay attention and inspire their children to perform better in school.…”
Section: Global Journal Of Educational Studiesmentioning
confidence: 99%
“…For example, the current policies on selecting honour students are based on DepEd orders or memoranda. These policies should be reviewed, amended, and institutionalized along with the university's admission policies, which is the best predictor of students' performance, according to Balasico and Tan (2020). It was also revealed that the laboratory school curriculum meets the minimum standard set by the Department of Education and the University Academic Council.…”
Section: Common and General Areasmentioning
confidence: 99%